KARAKTERISTIK KEWIRAUSAHAAN PENGUSAHA KECIL PAKAIAN JADI DI DEPOK, DAN PROSPEK USAHA DI MASA DEPAN - Zantermans Rajagukguk (Jurnal Kependudukan Indonesia, 2016)
To increase the numbers of entrepreneurs in Indonesia, the existence of small-scale apparel businesses in the township Bulak Timur, Depok becomes fascinating, as they naturally emerge and evolve, as well as face various problems with their abilities. However, lately, there are some concerns about whether they would be able to survive. Therefore, this article aims to identify the characteristics of small-scale apparel entrepreneurs in Bulak Timur, Depok City to understand their strengths, weaknesses, opportunities, and challenges that they experience. The results would then be formulated as strategies and conveyed to both business players and government. Respondents were selected using a simple random sampling by the number of 32 entrepreneurs (25% of the population). Primary data were collected using a survey method through face-to-face interview techniques, with the help of questionnaires and in-depth interview based on interview guidelines. Data collected was processed and analyzed by using descriptive statistics. The results of this study concluded that apparel entrepreneurs in Depok still have many weaknesses rather than strengths, which led to a lower value of their entrepreneurial characteristics. In addition, there are still many barriers faced in the development of entrepreneurship in Depok, including government policies and program that were not optimal. Further efforts must be made to grow small-scale businesses with high-value entrepreneurial characteristics in Depok. First, small-scale entrepreneurs should strive to build and enhance their entrepreneurial characteristics. They must also understand and implement survival management. Second, Depok City Government should provide support among other things by increasing business incubator and training on business management, including survival management; draw up a blueprint of small-scale businesses to prevent unfair competition, which can also be used as material to develop technopreneurship.